EXPLORING THE ASSOCIATION BETWEEN PREGNANCY SPACING, HISTORY OF DIABETES MELLITUS, AND OBESITY WITH THE INCIDENCE OF PREECLAMPSIA AT BULELENG DISTRICT HOSPITAL, BALI - Handayani, Putu Devi Sri; Shammakh, Adib Ahmad; Karmila, Dany; Farmanda, Irsandi Rizki (International Journal of Health Science & Medical Research, 2026)
Preeclampsia is a pregnancy complication that remains a major cause of maternal and infant morbidity and mortality; identifying risk factors that contribute to its occurrence is necessary. This study is novel in that it simultaneously analyzes the relationships among pregnancy spacing, diabetes mellitus, and obesity and the incidence of preeclampsia, and finds an opposite direction of the obesity relationship compared with most previous studies. This study aims to analyze the relationship between pregnancy spacing, diabetes mellitus, and obesity with the incidence of preeclampsia in pregnant and maternity mothers at Buleleng District Hospital. The Research method used is an observational-analytic case-control design, using medical record data for the period 2023–2024, with a sample size of 130 respondents: 65 preeclampsia cases and 65 controls without preeclampsia. Data analysis was performed univariately and bivariately using Fisher's Exact Test and Chi-Square with a significance level of P-value 0.05. The results showed that pregnancy spacing was significantly associated with preeclampsia incidence (P-value = 0.000), whereas diabetes mellitus was not (P-value = 0.492). Obesity showed a significant association with the incidence of preeclampsia, with an inverse relationship (P-value = 0.000). The conclusion of this study is that pregnancy spacing is a major risk factor for preeclampsia, while diabetes mellitus was not significantly associated, and obesity showed a significant inverse relationship; thus, regulating pregnancy spacing is an important strategy in efforts to prevent preeclampsia.